In-vitro biological screening of ethanol extract of Lagerstroemia thorelli leaves - Meem, M. M. Rubaiyat Muntasir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.